Makroalgers effekt på biologisk mångfald & friluftsliv på badstränder - Nilsson,Elin (2025)
The threat against biodiversity on beaches is significant in combination with the erosion pressing on our coastlines. At the same time beaches provide paramount cultural and recreational value and are expected to be attractive and accessible for beach visitors. This study explores macroalgae and the conflict between using the beach as a habitat to promote biodiversity while also promoting recreation. A web form was sent out to 25 municipalities in south of Sweden to investigate the management that is performed on the washed-up wrack on beaches. The questions aimed to find out how municipalities proceed with beach raking, what happens to the macroalgae after and whether they have performed any evaluation on how the management methods affects biodiversity. All 14 municipalities responded performed beach raking on either all or some of their beaches, mainly during the summer months. They all used mechanical methods, for example tractors, but the frequency varied between the municipalities from every day to only one or twice per season. When asked if the municipality actively works with preserving the biodiversity on the coastlines twelve answered yes, but only five of those also actively worked with macroalgae. However, the majority showed interest in further working to conserve the biodiversity that macroalgae support. Methods such as not removing the wrack from the beach and instead moving it to the side or using it to preserve coastal dunes have been shown to have positive effects on biodiversity. Leaving the macroalgae on the beach ensures that the nutrients and habitat it provides for plants, invertebrates and other macrofauna is still available and using the washed-up algae as support for the eroded dunes preserves habitat. However, leaving wrack to degrade may affect the reactional value for both aesthetics and comfort.
Keywords: Makroalger; Tång; Biologisk mångfald; Friluftslivspolitik